Morphological and morphometric aspects of rats brain in chronic organophosphate intoxication - Perez, Nilda M. (2006)
Subtle neurological disturbs are described in organophosphorus intoxication. Experimental studies have reported neuronal necrosis particularly in animals that present seizures. The objective of the present work was to investigate if rats (without seizures) exposed to an organophosphate agent, would have morphological changes of specific regions of the brain. The animals received 2,5 or 5,0 mg/kg of methamidophos, once a week, for 2 months and were decapitated after 2 months and 7 days of drug administration. We have observed atrophy of the molecular layer of the parietal cortex without neuronal loss in specific cerebral regions. This would be due to atrophy or loss of neuronal ramifications but without neuronal loss.